EE+EA : Enhancing the World Bank’s Energy Access Investments through Energy Efficiency - CLASP (World Bank, Washington, DC, 2015)
The World Bank (WB) has for many years been financing and conducting work to increase access to modern energy services among energy poor communities, and its efforts vary greatly from project to project, based largely on client-country context, requests, and needs. In mid-2014, CLASP evaluated a selection of recent WB EA projects to identify opportunities to expand and more effectively integrate and operationalize EE, a process and set of principles we refer to as EA+EE.